BOOK REVIEW: Power and Progress: Our Thousand-Year Struggle over Technology and Prosperity, by Daron Acemoglu and Simon Johnson, New York, NY, Public Affairs, 2023, 560 pp. ISBN-10: 1399804464, ISBN-13: 978-1399804462 - Domadenik Muren, Polona (Economic Annals, 2025)
BOOK REVIEW